PENGARUH CURRENT RATIO DAN DEBT EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT WILMAR CAHAYA INDONESIA Tbk PERIODE 2012-2021 - Marwi Oktaviyani; Ayu Puspa Lestiyadi (Journal of Research and Publication Innovation, 2025)
This research aims to determine the influence of the Current Ratio and Debt to Equity Ratio on Return On Equity at PT Wilmar Cahaya Indonesia Tbk. The data collection technique in this research uses statistical tests which include descriptive statistical analysis, classical assumption tests, linear regression analysis, and hypothesis testing. The results of this research show that partially the Current Ratio to Return On Equity Current Ratio (CR) has a tcount greater than ttable (3.016 > 1.945) with a significant value of 0.020 which is smaller than 0.05. So it can be concluded that the Current Ratio (CR) has a positive and significant effect on Return On Equity (ROE). The Debt To Equity Ratio to ROE shows that the test results of tcount are greater than ttable (2.453 > 1.945) with a significant value of 0.044 which is smaller than 0.05. So it can be concluded that the Debt To Equity Ratio (DER) has a positive and significant effect on Return On Equity (ROE). Simultaneously, the Current Ratio and Debt to Equity Ratio variables on Return On Equity show that the Fcount is greater than (12.037 > 4.74) with a significant value of 0.005 which is smaller than 0.05. So it can be concluded that simultaneously the Current Ratio (CR) and Debt To Equity Ratio (DER) have a significant influence on Return On Equity (ROE).